Genetic dissection of a Leishmania flagellar proteome demonstrates requirement for directional motility in sand fly infections. - Tom Beneke; François Demay; Edward Hookway; Nicole Ashman; Heather Jeffery; James Smith; Jessica Valli; Tomas Becvar; Jitka Myskova; Tereza Lestinova; Shahaan Shafiq; Jovana Sadlova; et al. (PLoS Pathogens, 2019)
The protozoan parasite Leishmania possesses a single flagellum, which is remodelled during the parasite's life cycle from a long motile flagellum in promastigote forms in the sand fly to a short immotile flagellum in amastigotes residing in mammalian phagocytes. This study examined the protein composition and in vivo function of the promastigote flagellum. Protein mass spectrometry and label free protein enrichment testing of isolated flagella and deflagellated cell bodies defined a flagellar proteome for L. mexicana promastigote forms (available via ProteomeXchange with identifier PXD011057). This information was used to generate a CRISPR-Cas9 knockout library of 100 mutants to screen for flagellar defects. This first large-scale knockout screen in a Leishmania sp. identified 56 mutants with altered swimming speed (52 reduced and 4 increased) and defined distinct mutant categories (faster swimmers, slower swimmers, slow uncoordinated swimmers and paralysed cells, including aflagellate promastigotes and cells with curled flagella and disruptions of the paraflagellar rod). Each mutant was tagged with a unique 17-nt barcode, providing a simple barcode sequencing (bar-seq) method for measuring the relative fitness of L. mexicana mutants in vivo. In mixed infections of the permissive sand fly vector Lutzomyia longipalpis, paralysed promastigotes and uncoordinated swimmers were severely diminished in the fly after defecation of the bloodmeal. Subsequent examination of flies infected with a single paralysed mutant lacking the central pair protein PF16 or an uncoordinated swimmer lacking the axonemal protein MBO2 showed that these promastigotes did not reach anterior regions of the fly alimentary tract. These data show that L. mexicana need directional motility for successful colonisation of sand flies.